Relazioni di patronato e la storia dell’antica Palestina: Dal modelo concettuale alle interpretazioni socio-politiche - Pfoh, Emanuel Oreste (2022)
Patron-client relationships have been well known in the field of social anthropology and political sociology since the middle of the 20th century. From the vast ethnographic documentation about this phenomenon, a schematic trait list of the extent and articulation of these socio-political relationships in ´´traditional´´ societies and communities can be organised. Now, what can the model of patronage or clientelistic bonds tell us about the political articulation and dynamics of ancient Palestine’s societies and political organisations? This paper, originating in a lecture at the University of Rome ´´La Sapienza´´, demonstrates the heuristic interpretative utility of this model of asymmetrical and reciprocal connections in two periods of Palestinian history, the Late Bronze Age and the Iron Age, drawing largely on their epigraphic evidence, but also exploring its validity for analysing certain aspects of the Hebrew Bible/the Old Testament.